Relationship between Coloring Play Therapy and Anxiety in Children during Hospitalization in the Melati Room, Sobirin Hospital, Kabupaten Musi Rawas - Maskur Hidayat; Yeni Eliyanti; Novega Novega (ANJANI Journal (Medical Science & Healthcare Studies), 2021)
The way to overcome anxiety caused by hospitalization is by playing with drawing and coloring pictures. The problem with research is that there are still children who feel anxious when they are treated. The purpose of this research is to know the relationship between Coloring Play Therapy and Anxiety in Children During Hospitality in The Jasmine Room Sobirin Hospital, Musi Rawas District. This type of research is cross-sectional study. The population was 1,050 people and the study sample was 91 children. The type of data used in research is to use primary and secondary data. Data analysis in this study used univariate and bivariate data analysis with the statistical method of chi square test at a significance level of 0.05. The results of this study were the majority of respondents (55.8%) who did not play coloring therapy in The Jasmine Room Sobirin Hospital, Musi Rawas District. Most of the respondents (61.6%) were worried about children when they were hospitalized in The Jasmine Room Sobirin Hospital, Musi Rawas District. Statistical test results obtained ρ = 0.0050 (ρ α 0.05), this shows that there is a relationship between coloring therapy and anxiety in children when hospitalized in The Jasmine Room Sobirin Hospital, Musi Rawas District. Researchers suggest that play therapy (drawing, coloring) can be used as an alternative therapeutic approach to reduce anxiety in children undergoing hospitalization.